2016
DOI: 10.1021/acsnano.5b05647
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Interfaces Do Not Alter Target Nerve Cells

Abstract: Neural-interfaces rely on the ability of electrodes to transduce stimuli into electrical patterns delivered to the brain. In addition to sensitivity to the stimuli, stability in the operating conditions and efficient charge transfer to neurons, the electrodes should not alter the physiological properties of the target tissue. Graphene is emerging as a promising material for neuro-interfacing applications, given its outstanding physico-chemical properties. Here, we use graphene-based substrates (GBSs) to interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 66 publications
6
151
0
Order By: Relevance
“…[145] Therefore graphene provides a flexible and conducting substrate that interfaces well with the soft, 3D biological systems. [146][147][148] For example, the mechanical flexibility and electrical functions of graphene membrane can be used to achieve a strongly coupled electromechanical biointerface by coating yeast cells with an ultrathin layer of rGO (see also Fig. 7f).…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[145] Therefore graphene provides a flexible and conducting substrate that interfaces well with the soft, 3D biological systems. [146][147][148] For example, the mechanical flexibility and electrical functions of graphene membrane can be used to achieve a strongly coupled electromechanical biointerface by coating yeast cells with an ultrathin layer of rGO (see also Fig. 7f).…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
“…[148] In fact, stimulating and recording extracellular potentials (or even intracellular potential using branched transistors [209] ) from neurons is one of the hallmark of modern bioelectronics. Graphene can serve not only as conductive electrodes to transduce stimuli into the cells, but also as the conductive channel of GFETs to monitor the presence and activity of the cells.…”
Section: Gfet Biological Cellular Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The film is then transferred on a 100-m glass coverslip. The protocol to obtain the ink is as follows [32], [33]: 120 mg of graphite flakes (Sigma-Aldrich) are dispersed in 10 mL of DIW with 90 mg sodium deoxycholate, then placed in an ultrasonic bath for 9 h and subsequently ultracentrifuged using a TH-641 swinging bucket rotor in a Sorvall WX-100 ultracentrifuge at 10 krpm (17 000g) for 1h. After ultracentrifugation, the top 70% of the dispersion is extracted by pipetting and then vacuum filtered via 100 nm pore-size filters (Millipore nitrocellulose filter membranes).…”
Section: B1 Broadband Pump-probe Spectroscopymentioning
confidence: 99%
“…Moreover, very few works have addressed the effect of uncoated graphene on the growth of neurons and glial cells. They reported that neurons can develop on graphene but their attachment was reduced compared to when the neurons were grown on poly- d -Lysine and laminin (Bendali et al, 2013; Sahni et al, 2013), that graphene stimulated neurite length compared to a glass substrate (Lee et al, 2015), or that pristine graphene and graphene-based substrates were permissive for neuronal outgrowth (Veliev et al, 2016) and synapse formation and function (Fabbro et al, 2016). …”
Section: Introductionmentioning
confidence: 99%